Позашлюбні зв'язки у Миргородському полку ХVIII ст. - Кручиненко, В. (Сiверянський лiтопис, 2018)
У статті на основі метричних книг і судових справ розглянуто проблему перелюбу
(позашлюбних зв'язків) на території Миргородського полку. З'ясовано, що релігійні заборони та осуд з боку громади не стали перепоною для подружніх зрад. В статье на основе метрических книг и судебных дел рассмотрена проблема прелюбодеяния (внебрачных связей) на территории Миргородского полка. Выяснено,
что религиозные запреты и осуждение со стороны общества не стали преградой для супружеских измен. In the article on the basis of metric books for the recording of born, married, deceased
parishioners and court cases the problem of adultery (extramarital relations) in the territory
of the Myrgorod regiment was analyzed. After studying this question, the author concluded
that religious prohibitions and condemnation on the part of the comrades did not become an
obstacle to marital treasons.